COLLECTION OF YOUNG BILLFISHES FROM VIZHINGAM - Bennet, P Sam (Indian Journal of Fisheries, 2011)
Young billfishes collected at Vizhingam have been assigned to the genus Tetra- /)/urÂ«^, but their specific identity could not be established. A general description of the specimens has been given